Kajian Kriminologi Terhadap Tindak Pidana Pencurian Sepeda Motor - Tri Fahtur Rohman; Muazzul Muazzul; Wessy Trisna (Universitas Medan Area, 2021)
Criminology covers a wide and diverse range of studies, causing criminology to be an interdisciplinary study of crime. Criminology does not only stop at the description of events and forms of crime on the surface, but also reaches traces of the causes or roots of the crime itself both from individuals and from sources of social, cultural, political and economic conditions, including various government policies (including legal formulation and law enforcement). Theft is taking something, which is wholly or partly owned by someone else, with the intention of being owned illegally, factors causing the occurrence of theft include educational factor, economic factor, social factor. The problem in writing this thesis is how the legal process of the crime of theft of motor vehicles in the case of the decision number: 1381/Pid.B/2017/PNMdn and how to deal with the crime of motor vehicle theft. The method used is normative juridical, namely research focused on examining the application of applicable rules or norms in positive law. The type of normative juridical research is carried out by examining various formal legal rules such as laws, regulations and literature which contins theoretical concepts which are then related to the problems that will be discussed in this study.